The effect of foliar spray with some nutrients and citric acid on the physical and chemical properties of the citrus paradise grafted on citrumelo as root stock - نبيعه عمار; علي ديب; علي الخطيب (Latakia University Journal -Biological Sciences Series, 2023)
The study was carried out during (2020 and 2021) at Setkhiris village which belonging to the countryside of Lattakia Governorate, in citrus orchard containing (36) trees of citrus paradise at the age of 25 years old and grafted on citrumelo as root stock, to study the impact of foliar spray with mixture of macronutrients (N,P,K) , mixture of micronutrients (Fe,B,Mg,Zn) and citric acid , on the physical and chemical properties of citrus paradise, The results showed that the treatments significantly raised fruit volum and the percent of juice compared to the control, at treatment of multi fertilization with mixture of macronutrients, mixture of micronutrients and citric acid spray achieved the highest fruit weight (349g) and the highest fruit size (420.67 cm3). mixture of macronutrients and citric acid treatments gave best results of total soluble solids(9.77%) and the highest acidity of the juice(1.6%).